Gonial angle and mandibular ramus height in Surabaya population: comparison and correlation analysis in panoramic radiograph - Chusida, An'nisaa; Kurniawan, Arofi; Rizky, Beta Novia; Pribadi, Salma Nailah Pradnya; Diva, Annisa Tiara; Anandhiyah, Haura Destina; Alias, Aspalilah (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
One of the crucial steps of identifying an individual is to determine their sex. The mandible, which is the largest and strongest bone in the human face, is a useful tool due to its significant sexual dimorphism. Two features that are recognized for their high sexual dimorphism are the gonial angle and mandibular ramus height. Several studies have shown different results when using both measures to estimate sex, factors that are thought to influence morphological differences include age, population, sex, and physical activity. The objective of this study was to analyze the differences in gonial angle and mandibular ramus height between sexes using panoramic radiography. Additionally, it aimed to analyze the correlation between these measurements and sex. The measurements of the gonial angle and mandibular ramus height were conducted using ImageJ software. Initially, the specific anatomical landmarks were identified, and the software’s measurement tools were then employed to accurately assess the height and angle based on these selected points. The sample consisted of secondary data obtained from 70 panoramic radiographs of patients aged 20–45 years at the Dental and Oral Teaching Hospital (RSGMP) of Universitas Airlangga, Surabaya. Data analysis was conducted using the independent t-test and Pearson correlation. There was a significant difference in the mandibular ramus height between sexes, with males having a greater height (p < 0.05). It was also discovered that, despite the fact that males exhibited a smaller gonial angle compared to females, this difference was not statistically significant (p = 0.29). Furthermore, a significant correlation was observed between mandibular ramus height and sex (r = 0.498); however, there was no significant correlation between gonial angle and sex (r = -0.128). The study reveals a significant difference in mandibular ramus height between males and females, with males exhibiting greater height. This parameter shows a strong correlation with sex, making it a reliable indicator for sex determination. Conversely, the gonial angle is not suitable for this purpose.